Scale dependence of gully investigations - Jakab, Gergely; Kertész, Ádám; Szalai, Zoltán (Hungarian Geographical Bulletin, 2010)
Soil erosion causes considerable damage both for the agriculture by soil loss and for the environment by sedimentation via contribution to eutrophication. Disastrous soil erosion events due to extremely high intensity rainfalls have recently posed serious danger to roads, dams, and edifices in Hungary. Gully erosion plays a particular role in rapid and extreme erosion processes. Research at regional, catchment or gully scale may have different objectives. The main aim of this paper is to compare methods from the local to regional scale. Three case studies are presented. The results suggest the following statements to be made. At local scale the processes are determined by gully morphology, material and energy transport as well as by soil properties. The topographical and lithological factors parallel with land use have growing importance with the decreasing scale.